The Existence of Keroncong Music in The City of Sawahlunto (2012 – 2023) - Tasiyah, Diana; Erawati, Meri (MSJ : Majority Science Journal, 2024)
This article discusses the existence of Keroncong music in Sawahlunto City 2012 – 2023. This research uses heuristic research methods, source criticism, interpretation, historiography. Based on the research results, it can be concluded: The research results show that musical arts in Sawahlunto City originate from ethnic Javanese workers who are employed in mines. These workers eventually formed the Keroncong Orchestra group, which was first formed in the 1940s and consisted of only ethnic Javanese people. However, over time, cultural acculturation occurred, including the use of tools, players and songs used in Keroncong music. Keroncong in the city continues to feel strongly tied to local customs, and is often featured in community-involved events and festivals, highlighting the original and unique aspects of the region. 3) From a perspective outside Sawahlunto City, keroncong music tends to be made by incorporating modern elements and collaboration with other genres, making it more easily accepted by the general public.